Handling Stunting in Policy Perspective in Sinjai District - Djohar Djohar; Dety Junita Sulanjari; Kurnia Kurnia; Ahmad Syaekhu (Universitas Negeri Makassar, 2022)
The problem of stunting cannot only be solved through nutrition programs, but must be integrated with other programs This study aims to analyze the implementation of policies in handling stunting in Sinjai District. Therefore, this study uses qualitative research methods with observational data collection techniques, interviews and documents. As for data analysis techniques, namely data reduction, data presentation, and conclusions. Based on the results of the study, it is known that overall the indicators that are variables in the implementation of policies in handling stunting in Sinjai Regency are quite good, this can be seen from the effectiveness of intense communication carried out by the government to regional device organization who has responsibility, in addition to adequate resource coverage so that the objectives of the policy can be realized, namely the reduction in stunting rates in Sinjai Regency and the existence of good despositions and bureaucratic structures so that the objectives of policy implementation can be achieved.